Clinical and Pathophysiological Correlations in Acute Stroke, CT Visualized at Different Times - S. A. Rumyantseva; E. V. Silina; N. A. Gomboeva; V. A. Stupin; YU. D. Vasiliev; A. L. Kovalenko; E. N. Kabaeva (Антибиотики и Химиотерапия, 2020)
Two hundred twenty one patients aged 32-93 years with brain infarction, admitted to a Vascular Neurology Center in the first 3-48 hours (mean 6 hours) after the onset of the symptoms of stroke with computed tomography (CT) verified diagnosis were enrolled in the study. According to the timing of the CT-verification the patients were divided into 2 groups: «early» visualization (EV 50.2%) and «late» visualization (LV, 49.8%). In the EV group the lesion was visualized by CT on the admission (3-6 hours after the admission), in the LV group it was visualized only when CT was repeated 2-3 days after the admission. The patients in the LV group demonstrated increased severity of the underlying pathology, increased mortality and unfavourable functional outcomes correlating with the stroke lesion volume vs. the EV group. There was observed pathophysiological correlation of the blood enzymatic spectrum and acid-base balance parameters, explaining the late lesion visualization by delayed and more pronounced intracellular energy synthesis stabilization mechanisms failure in the aerobic and anaerobic glycolysis cycles.